2020
DOI: 10.1177/0021998320946368
|View full text |Cite
|
Sign up to set email alerts
|

Study of the pull-out test of multifilament yarns embedded in cementitious matrix

Abstract: In order to understand the impregnation mechanism of a yarn by a cementitious matrix and its influence on the mechanical properties of a yarn/cement composite, pull-out tests have been performed on samples of yarn/cement. Two embedded lengths for the yarn and different rheological and mechanical properties for the matrix were tested. Two pull-out modes were distinguished according to the compressive strength of matrices. For matrices with a compressive strength between 60 and 70 MPa the pull-out mode is charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…It is not the case for the matrices with cement and calcareous filler. For those matrices, the main parameters influencing the results are the fluidity of the matrix and the embedded length of the samples (see Slama et al., 7 ). It was explained by the fact that a higher embedded length and a higher fluidity both lead to more filaments/matrix bonds, and so higher P max values.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is not the case for the matrices with cement and calcareous filler. For those matrices, the main parameters influencing the results are the fluidity of the matrix and the embedded length of the samples (see Slama et al., 7 ). It was explained by the fact that a higher embedded length and a higher fluidity both lead to more filaments/matrix bonds, and so higher P max values.…”
Section: Resultsmentioning
confidence: 99%
“…For matrices with 100% of cement, it was found that one of the parameters influencing the P max values is the matrix mechanical properties, and especially its compres-F I G U R E 5 P max according to the number of fully impregnated filaments, error bars are the standard deviation sive strength (see Slama et al, 7 ). It was explained by the fact that, for those strong matrices, the filament/matrix bond strength is high and it determines the results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations